Optic neuritis: a narrative review on biomarkers and imaging in differential diagnosis (Research, Society and Development, 2025)
Optic neuritis (ON), an acute inflammation of the optic nerve, is the most common optic neuropathy in young adults and constitutes a neuro-ophthalmologic emergency. For years, ON was viewed primarily as a sentinel event for Multiple Sclerosis (MS). However, recent discoveries, particularly serum antibodies against aquaporin-4 (AQP4-IgG) and myelin oligodendrocyte glycoprotein (MOG-IgG), have redefined the diagnostic landscape. This narrative review aims to synthesize the most recent scientific evidence (2020-2024) on the ON approach, focusing on the clinical, serological, and imaging findings that differentiate these etiologies. Methods: A narrative review was conducted, searching PubMed, SciELO, and LILACS for publications from 2020 to 2024 using relevant descriptors. Results: The synthesized literature indicates that atypical presentations (such as bilaterality, severe vision loss, pronounced papillitis, poor recovery) mandate immediate serological investigation. MOGAD-ON often presents with significant disc edema but a strong steroid response, whereas NMOSD-ON (AQP4+) is linked to a poor visual prognosis and high relapse risk. Tools like Optical Coherence Tomography (OCT) are essential for quantifying axonal damage (retinal nerve fiber layer), which is demonstrably more severe in NMOSD. Therapeutic management differs drastically; MS therapies can be ineffective or harmful in NMOSD. Conclusion: The approach to optic neuritis is no longer monolithic. The ophthalmologist plays a central role in the initial suspicion and must use biomarkers and imaging (OCT, MRI) for precise etiological classification, which dictates acute therapy and the need for chronic immunosuppression.